Group Size and Adult International Field Study Programs: A Literature Review - Natalia Mora; Brittany Davis; Joellen E. Coryell PhD (Adult Education Research Conference, 2017)
Traveling in a group impacts the learning process abroad. This literature review examines established research about the effects of group sizes on learning when studying abroad as an adult.
Keywords: Group size abroad; multicultural learning abroad; effects of group size; cultural self-awareness and learning; group and individual learning abroad.